KAJIAN CSR MELALUI SUDUT PANDANG PERENCANAAN TRANSAKTIF: STUDI KASUS PERENCANAAN CSR DI INDONESIA - Taufiq, Muhammad; Suhirman; Sofhani, Tubagus Furqon; Kombaitan, Benedictus (School of Accountancy, University of Agung Podomoro, 2019)
CSR gain local community development. However, its practice is contradictive, partially not onlybeneficial but also it does not bring significant benefits. CSR planning as an integration tool for theinterest between corporate and local community is the main driving factor for its effectivityimplementation. The article presents a communicative approach in CSR planning by combining boththe concept of CSR and transactive planning. The general view that Corporate dominating CSRplanning is the main criticism which causes its policy has not a significant impact. How is theconceptualization of CSR planning approach, which communicates with the beneficiary community,this article aims to reveal its understanding. The study evaluates the transactive process on CSRplanning, through descriptive qualitative analysis of literature. The result proposes a CSR planningmodel based on transactive planning approach. The article also initiates that CSR planning is atransactive process which raised through knowledge transaction between planner and communitytoward towards legitimacy in increasing community support for company operations.